Knowledge, attitude, and practice toward social media use in dental education - Sayed Abrar; Harsh Parmar; Gulam Anwar Naviwala; Kishor Sapkale; Surabhi Nabazza; Manoj M Ramugade (Wolters Kluwer Medknow Publications, 2020)
Introduction: The use of social media has been a revolutionary way of communication, since the past decade. Considering its high level of usage among the younger individuals, social media may provide a unique method of learning for dental students. However, the perception of dental educators on the usage of social media and networking sites is unknown. Hence, this study was conducted to assess the knowledge, attitude, and practice of dental faculty and residents toward social media use in dental education. Materials and Methods: This cross-sectional study was conducted in Government Dental College and Hospital, Mumbai, from November 2019 to December 2019. The questionnaire was prepared and validated before conducting the study. All the faculty members and the residents of the college were included in the study. The questionnaire was based on three dimensions (knowledge, attitude, and practice) and assessed the views of participants on the social media usage. Results: A total of 65 participants were included in the study, where 32 were faculty members and 33 were residents. The mean age of the participants was 31.52 ± 6.589. Out of the total, 26 (40%) participants were male and 39 (60%) were female. The mean experience of the study participants was 4.71 ± 5.997. The responses were compared between residents and faculty and the responses were similar for most knowledge, attitude, and practice question. The residents were keener on looking forward to developing social media as a primary aid in dental education compared to the faculty (P = 0.029). Conclusion: Due to ease of use and widespread applicability, social media now has a great potential to deliver educational content. This study demonstrates the positive responses of the faculty towards social media usage and further enhances traditional education.